The Klondike gold fields map of Alaska / Poole Bros. - Poole Brothers (Poole Bros., 1898)
Published for the Northern Pacific Railway Co. Relief shown by land forms and shading. Insets: Taiya and Skagway trails -- United States placer mining law. Verso: The key to Klondike, route map of the Northern Pacific Railway, text and illustrations Color 1:4,224,000